Spontaneous Bio-Recycling: Recovering Bioactive Molecules Through Endogenous Microbial Maceration of Hemp Residues - Leonardo Donati; Angela Conti; Debora Casagrande Pierantoni; Chiara Ruspi; Martina Cerri; Carla Emiliani; Gianluigi Cardinali; Laura Corte (Microorganisms)
Biomass residues represent a major issue for industries. On the other hand, residues enclosed major classes of bioactive compounds that could be extracted and used across various fields. This study aimed to elucidate the role of the endogenous microbial community in the lignocellulosic degradation of hemp residues for biorefineries or other industrial processes, simultaneously characterizing the composition of three extracts recovered at different stages of maceration. The process was examined from different perspectives: plant tissue degradation and microbial dynamics were monitored using histological, cultural-dependent, and independent analysis. Extracts were characterized through FTIR, NMR, and SDS-PAGE analyses, also evaluating their potential as biostimulants for microbial growth. Results revealed that the composition of the endogenous prokaryotic community remained stable during the maceration period, while fluctuations in various fungal genera were observed. The taxonomical composition of hemp residues at different stages may account for the increased accumulation of amide-containing compounds, sugars, and other metabolites detected in long-term bioconversion. Finally, the extracts recovered from the microbial degradation of hemp residues were able to support the growth of the yeast Cryptococcus phenolicus and the bacterium Peribacillus simplex as the sole source of nitrogen, paving the way for their potential use as biostimulants.